Factors, Nature and Impacts of Slum Dwellers Residential Mobility within the Dhaka City (International Journal of Built Environment and Sustainability, 2019)
The pattern of residential mobility varies throughout the world. Slum populations consistently report higher rates of residential mobility than other populations. However, the pattern and the consequences of residential mobility of the slum dwellers are not well studied. Dhaka, the Capital of Bangladesh, has a large population, more than 14 million of which about 1.06 million live in slums with an increase of 60.73 percent in the last 17 years. The objectives of this study are: (1) to identify the significant factors of residential mobility of slum dwellers; and (2) to examine the patterns of residential mobility of slum dwellers in three slums area located in Dhaka. This study further analyzed the impacts of residential mobility on the socio-economic aspect of the slum dwellers. For this research purpose, 267 households from three slums of Dhaka namely Kallyanpur slum, Agargaon slum, and Karwan Bazar railgate slum were selected through non-probability convenience sampling and interviewed. This study found that residential mobility was influenced by factors which are related to life cycle; employment, income and distress; land tenure and homeownership; neighbourhood condition and grouping issues. Among all the studied variables the most five significant factors influencing residential mobility are slum eviction, unavailability of utility services, marriage, changing job and getting homeownership status. It is revealed that the nature of the residential mobility for the surveyed slum dwellers is mainly negative and it poses a significant impact on the socio-economic aspects of life. The findings of the study pave the way to recommend specific measures for the slum dwellers to improve their condition by lessening the negative impacts of residential mobility.
Keywords: Residential mobility; Slum; Life-course perspective; Dhaka